Comparative Study on Cryosurgery with Carbamazepine and Alcohol injection in Trigeminal Neuralgia - Hossain, M A; Molla, M R; Akther, M; Haider, M N (Bangladesh Journal of Medical Science, 2012)
Objectives: To assess the efficacy of Cryosurgery for the treatment of Trigeminal neuralgia and to compare this procedure with Carbamazepine and alcohol block. Materials and method-A prospective study with 75 cases of Trigeminal neuralgia was carried out in the Department of Oral and Maxillofacial Surgery, Bangabandhu Sheikh Mujib Medical University from January 2006 to December 2007. Out of 75 cases 25 treated with Carbamazepine only, starting dose 100 mg b.d. with incremental dose up to 800 mg, 25 received alcohol block with maintenance dose of Carbamazepine 200 mg b.d. over the study period and 25 received Cryosurgery with initial maintenance dose of Carbamazepine 100 mg b.d. then tappered on 1st follow up visits and withdrawn on the 2nd follow up visits. Visual linear analogue scale (VAS) was used to measure pain intensity in different groups. Results: Out of different treatment modalities on follow up onwards pain control was better in Cryosurgery than Carbamazepine and alcohol block. Conclusion: This study reveals that the efficacy of Cryosurgery is better than Carbamazepine and alcohol block to eliminate the pain intensity in Trigeminal neuralgia. DOI: http://dx.doi.org/10.3329/bjms.v11i3.11721 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12